ChemInform Abstract: Transfer Reaction Studies with Spectrometers. Issue 38 (10th September 2014) - Szilner, S.; Corradi, L.; Pollarolo, G.; Fioretto, E.; Stefanini, A. M.; de Angelis, G.; Valiente‐Dobon, J. J.; Farnea, E.; Lunardi, S.; Mengoni, D.; et al., et al.
Abstract Review: 22 refs.